Interfaced Motive of the Terrorism Threat in the Case of Policing by Densus 88 Anti-Terror - Ridwan, Wachid; Murod, Makmun (Universitas Muhammadiyah Yogyakarta, 2024)
Throughout 2021, the Special Detachment (Densus) 88 Anti-Terror of the National Police of the Republic of Indonesia carried out firm policing regarding the threat of violence as mandated by Law No. 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. This study aims to unveil the interfaced motive of violating the mentioned law by suspects having proximity to Muhammadiyah family members in Yogyakarta, Makassar, and Surabaya. This study also revealed factors of the interfaced motive of the terrorism threat by conducting both observation and in-depth interviews with three suspects held in the custody of the Regional Police Jakarta. The ideological motive, the desire to fasten the practice of Islamic Sharia in Indonesia, became a crucial finding holding similarities with da’wah promoting good and preventing vice (amar makruf nahi munkar) in Muhammadiyah. The euphoria of the new emergence of the Islamic State in Iraq and Syria came as the subsequent finding, followed by the figure of preachers outside Muhammadiyah. These three interfaced motives emerged as the etiquette background of the suspects for a long period. The confessions of the suspects revealed that they had no intention of committing crimes. However, they were in a group and strongly prone to extremism and terrorism.